2012
DOI: 10.1111/j.1750-3841.2012.02836.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Effects of Hexanal Vapor on Fresh‐Cut Slices of Golden Delicious Apples

Abstract: Hexanal is a natural antimicrobial molecule that characterizes apples aroma. In this paper, the sensory effects of hexanal, as a component of packaging atmosphere, on fresh sliced Golden Delicious apples after storage at 4 °C for 8 d were evaluated. In particular, a colorimetric analysis of slices treated with different concentrations of hexanal vapor (coming from 3.040 to 0.076 mmol of liquid aldehyde per liter of air) fixed at 0.076 mmol/L the amount of hexanal in evaluating sensory effects in the subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In addition, colorimetric tests carried out collaterally to this work showed that the employed concentration of hexanal exerts no influence on the color of the slices treated with the anti‐browning mix (data not shown), in agreement with the negligible positive effect of small concentrations of hexanal vapor alone on the original color retention of fresh‐cut apple slices (Musetti and Fava ). The combination of the 0.076 mmol of hexanal per liter of air and the anti‐browning mix does not even determine substantial changes in the fruit respiration, in agreement with the precursor role of hexanal (it is not an inductor) in the synthesis of esters, thus allowing the establishment of a passive atmosphere suitable for the preservation of the sensory quality of fresh‐cut product (Musetti and Fava ).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…In addition, colorimetric tests carried out collaterally to this work showed that the employed concentration of hexanal exerts no influence on the color of the slices treated with the anti‐browning mix (data not shown), in agreement with the negligible positive effect of small concentrations of hexanal vapor alone on the original color retention of fresh‐cut apple slices (Musetti and Fava ). The combination of the 0.076 mmol of hexanal per liter of air and the anti‐browning mix does not even determine substantial changes in the fruit respiration, in agreement with the precursor role of hexanal (it is not an inductor) in the synthesis of esters, thus allowing the establishment of a passive atmosphere suitable for the preservation of the sensory quality of fresh‐cut product (Musetti and Fava ).…”
Section: Resultssupporting
confidence: 76%
“…To treat the Golden Delicious apple slices, the highest concentration of α‐lipoic acid usable in aqueous solution (970 μM) was selected on the basis of an unstructured sensory evaluation performed by seven members of our in‐house selected sensory panel (Musetti and Fava ) on samples treated with its respective water‐soluble sodium salt, coupled with a concentration of ascorbic acid (57 mM) similar to the lowest ones able to exert an anti‐browning effect reported in literature on minimally processed fruits (Soliva‐Fortuny and Martín‐Belloso ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the ability of nanoporous-crystalline polymer films to induce chemical stability to their guest molecules is for the first time revealed. Chemical stabilization is often deserved for antimicrobials, which are widely used for many applications , including food protection. , In particular, hexanal, an aldehyde present in fruits and vegetables, has toxic action toward parasites that attack the fruit and cause it to fall. , It has been also shown that the addition of this compound in food packaging systems containing fresh fruits has a positive effect on their shelf life. In fact, it has a significant inhibitory effect against pathogenic microorganisms often isolated from raw materials ( E. coli , S. enteritidis , and L. monocytogenes ), and it also shows antifungal activity against A. niger. Hexanal, however, is an unstable molecule which suffers the problem of poor stability to oxidation already in air at room temperature, so it must be generally preserved at low temperatures (in the range 2–8 °C).…”
Section: Introductionmentioning
confidence: 99%
“…In PN and SX, the ethanol content is lower than that in LD, whereas the content of 2-Hexen-1-ol is higher than that in LD. Among them, hexanal is a natural antibacterial molecule with a fresh, fruity aroma (Musetti and Fava 2012), whereas benzaldehyde has an aroma similar to bitter almonds (S anchez-P erez et al 2010). Furthermore, 2-hexen-1-ol had a strong fruit smell that can be used to prepare apple and other fruit-type essences.…”
Section: Resultsmentioning
confidence: 99%